ANALISIS KETIDAKSTABILAN TEGANGAN DAN FREKUENSI PADA PEMBANGKIT LISTRIK TENAGA MIKROHIDRO (PLTMH) ANDUNGBIRU KECAMATAN TIRIS KABUPATEN PROBOLINGGO - Muhammad Ryan Al Hafidz; Rini Nur Hasanah; Lunde Ardhenta (Jurnal Mahasiswa TEUB, 2023)
Microhydro Power Plant (MHPP) is a small-scale power plant that is environmentally friendly which utilizes the existing water discharge around us to be converted into electrical energy such as irrigation canals or rivers. Because the small-scale MHPP tends to use synchronous generators which are relatively affordable. When a synchronous generator is subjected to a load of varying magnitude, the magnitude of the voltage will also vary. This causes voltage and frequency instability in the MHPP. This study will use MHPP Andungbiru Unit A2, Tiris District, Probolinggo Regency as a test object with a descriptive research type through a quantitative approach which aims to provide an overview of the voltage and frequency instability that occurs. The results of this study indicate that the highest/lowest voltage and frequency instability values, namely 274.6 volts/53 Hz and 118.5 volts/27.67 Hz, are due to the influence of changes in load current. This can cause the generator rotational speed to fluctuate, causing the resulting voltage and frequency to become unstable. The solution is to add water power to rotate the turbine shaft and rotate the generator faster so that it can reduce the value of the voltage drop caused by losses on the turbine and generator parts. This is because large electric power can increase the voltage and frequency without having to adjust the load. Additional water power can be done by making improvements to civil parts so that they comply with standardization. In addition, improvements to the electrical part, namely improvements to the ELC system, can also be used to achieve stable and more efficient voltage and frequency values. Keywords — MHPP, Synchronous Generator, Voltage, Frequency